Giant mucinous cystadenocarcinoma of ovary: A case report and review of literature - Rajshree Dayanand Katke (Wolters Kluwer Medknow Publications, 2016)
Giant cystadenocarcinomas of the ovary are rarely described. Huge ovarian masses are mostly benign, but malignancy should be ruled out by investigations and clinical assessment. Giant cysts require resection because of compressive symptoms or risk of malignancy and their management invariably requires laparotomy to prevent perforation and spillage of the cyst fluid into peritoneal cavity. Here, we present a case of a 42-year-old female with severe and rapidly growing abdominal distension operated for exploratory laparotomy for cystic mass excision. On histology, mass was found to be metastatic mucinous cystadenocarcinoma with omental metastasis. The diagnostic and management challenges posed by this unexpected and unusual presentation of an ovarian cystadenocarcinoma are discussed. The main aim of this report is to draw attention to huge ovarian epithelial cysts with unsuspected presentation contributing to a decrease in any underdiagnosis, misdiagnosis, and mismanagement that might occur.